Activity Test of the Preparation of Dental Passage Gel Extract of Basil Leaf Ethanol (Ocimum Basilicum L.) Againts Staphylococcus Aureus - Rosita Irianti Dehi; Alvernia Dwi Maulana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Based on this, basil leaves are formulated in gel toothpaste preparations that have antibacterial activity.This study aims to determine the antibacterial activity of basil leaf gel toothpaste with various baseh concentrations, 20%, 40% and 60% and to determine the best concentration of basil leaf extract in gel toothpaste preparations that have antibacterial activity against Staphylococcus aureus. Basil leaves were extracted by maceration method using 96% ethanol solvent which was then tested for antibacterial activity using disc diffusion method with Ciprofloxacin as a positive control and aquadest as a negative control. The results of antibacterial testing showed that the mouthwash with base concentration did not produce an inhibition zone, 20% had a diameter of 6.68 mm, a concentration of 40% had a diameter of 7.81 mm and 60% had a diameter of 8.77 mm. The greater the concentration, the larger the resulting inhibition zone. In this study, it can be concluded that the gel toothpaste of basil leaf extract (Ocimum basilicum L.) which can inhibit the Staphylococcus aureus is at a concentration of 60% with a moderate inhibitory response category